STRATEGI PENGUATAN UMKM DESA LABULIA MAKMUR BERBASIS DIGITAL MARKETING MELALUI PELATIHAN PEMBUATAN LOGO DAN BRANDING PRODUK - Cahaya Safari; Isma Evita Febriani; Fathurrahman; M. Fajar Aulia; Armeyta Dwicahyani; Muhamad Arif Izaz Putrawan; Riza Aprilia; Maulana Siregar; Lilik Huriani; Kesy Alawiya; Maria Ulfa (Universitas Mataram, 2026)
The development of digital technology requires Micro, Small, and Medium Enterprises (MSMEs) in rural areas to adapt to product marketing. Branding and visual identity have become essential elements in enhancing the competitiveness of MSMEs in the digital era. Labulia Village, Jonggat District, Central Lombok Regency, has diverse MSME potential; however, most business actors still face limitations in logo creation and the use of digital media. This condition impacts the low added value and limited market reach of their products. This community service activity was carried out by students participating in the Community Service Program (KKN) of the University of Mataram, together with field supervisors, to improve the knowledge, skills, and readiness of MSME actors in Labulia Village in creating logos and product branding as a strategy to strengthen MSMEs based on digital marketing. The methods included socialization of branding concepts, hands-on training using the Canva application on smartphones, and evaluation through pre-test and post-tests. The activity involved 41 participants, consisting of MSME actors, homemakers, youth, village officials, and the general public. The results showed an increase in the average participant score from 3.79 in the pre-test to 4.22 in the post-test, representing an improvement of 11.33%. Participants demonstrated increased understanding of the function of logos, the role of branding in enhancing product value, and the use of digital media. They were also able to independently design simple logos and understand their application in packaging and digital promotional media. This activity proved effective in improving branding literacy and digital readiness among rural MSME actors as an initial step toward strengthening competitiveness and expanding market reach.